ON SOME NONLINEAR AND NONCLASSICAL EQUATIONS OF HEAT DIFFUSION - Akbarov Ummatali Yigitaliyevich; Samatova Azima Rasuljon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, some non-linear and non-classical equations representing the heat dissipation process are shown.